Optimasi Produksi Migas Dengan Permanent Coiled Tubing Gas Lift Pada Sumur “VR-03” Lapangan Wacana - Vely Remitha; Deny Fatryanto Edyzoh Eko Widodo; Teddy Kurniawan; Fatma; Rohima Sera Afifah; Viola Sri Wahyuni; Pratama Bagus Restu.S (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
The VR-03 well in the "WACANA" field is a well that has the potential to produce oil and gas. However, over time, the pressure on the VR-03 well is no longer able to flow fluid to the surface in a natural flow, so an artificial lift method is needed to help lift oil and gas to the surface. As an effort to help lift oil and gas to the surface, the permanent coioled tubing gas lift method was applied to the VR-03 well. Permanent coiled tubing gas lift is the most effective and economical injection method to be carried out on the "VR-03" well because of its simple installation and judging from the available parameters such as the size of the cooiled tubing, kick off point, and top node pressure which will make the "VR-03" well more optimal. After a PCTGL design planning simulation is done the oil flow rate has increased from previously no flow to 265.3 STB/day. With a maximum depth of gas injection point at a depth of 4900 ft and an optimum gas injection rate 2.85 MMscf/day.